Foreceasting Produksi Padi Di Kecamatan Amanuban Selatan Kab.Tts Menggunakan Metode Least Square - Yermias Jaher Ite Leuhoe (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
Foreceasting is a method of predicting what will happen in the future. Forecasting is necessary because there is a difference in the time gap between the awareness of the need for a new policy and the timing of the implementation of the policy. Forecasting is widely used, one of which is in forecasting the level of rice production in South Amanuban District, so that the government can find out the level of rice production in South Amanuban District in the future. Rice is a very important cultivated plant for mankind.rice is the main source of food for almost half of the world's population.including Indonesia, rice is one of the staple foods of the Indonesian people, especially in the South Amanuban district. The purpose of this study is to forecast the level of rice production in South Amanuban District in 2021-2026 with the Least Square Method To calculate the error value of the forecasting used Mean Absolute Percentage Error. The data used in this study is secondary data, with data taken from 2010 to 2020, the amount of rice production in the next six years will be predicted, namely from 2021-2026.The results of the study show that forecasting using the Least Square method that the amount of Rice Production in South Amanuban District in 2021 is estimated to be 16718,7 kg or 16,7187 ton , in 2022 as much as 17127,1 kg or 17,1271 tons, in 2023 as many as 17535,5 kg or 17,5355 tons, in 2024 as many as 17943,9 kg or 17,9439 tons, in 2025 as many as 1835,2 kg or 18,3523 tons and in 2026 as many as 18760,7 kg or 18,7607 tons. With an error value calculation of 11%, using MAPE calculations. Keywords – Forecasting,Production,Rice,Least Square Method